The use of resuscitative endovascular balloon occlusion of the aorta (REBOA) for non‐traumatic cardiac arrest: A review - Craig D. Nowadly; M. Austin Johnson; Guillaume L. Hoareau; James E Manning; James I. Daley (Journal of the American College of Emergency Physicians Open)
Abstract Resuscitative endovascular balloon occlusion of the aorta (REBOA) has been proposed as a novel approach to managing non‐traumatic cardiac arrest (NTCA). During cardiac arrest, cardiac output ceases and perfusion of vital organs is compromised. Traditional advanced cardiac life support (ACLS) measures and cardiopulmonary resuscitation are often unable to achieve return of spontaneous circulation (ROSC). During insertion of REBOA a balloon‐tipped catheter is placed into the femoral artery and advanced in a retrograde manner into the aorta while the patient is undergoing cardiopulmonary resuscitation (CPR). The balloon is then inflated to fully occlude the aorta. The literature surrounding the use of aortic occlusion in non‐traumatic cardiac arrest is limited to animal studies, case reports and one recent non‐controlled feasibility trial. In both human and animal studies, preliminary data show that REBOA may improve coronary and cerebral perfusion pressures and key physiologic parameters during cardiac arrest resuscitation, and animal data have demonstrated improved rates of ROSC. Multiple questions remain before REBOA can be considered as an adjunct to ACLS. If demonstrated to be effective clinically, REBOA represents a potentially cost‐effective and generalizable intervention that may improve quality of life for patients with non‐traumatic cardiac arrest.